2007
DOI: 10.1128/ec.00162-07
|View full text |Cite
|
Sign up to set email alerts
|

Capsule Structural Heterogeneity and Antigenic Variation in Cryptococcus neoformans

Abstract: Cryptococcus neoformans is a human pathogenic fungus with a capsule composed primarily of glucuronoxylomannan (GXM) that is important for virulence. Current views of GXM structure postulate a polymer composed of repeating mannose trisaccharide motifs bearing a single ␤(1,2) glucuronic acid with variable xylose and O-acetyl substitutions to form six triads. GXM from different strains is notoriously variable in triad composition, but it is not known if the polymer consists of one or more motif-repeating units. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 30 publications
6
98
0
1
Order By: Relevance
“…Consistent with this view are the findings that Oacetylation of alginate in Pseudomonas aeruginosa contributed to biofilm formation [19] and the C. neoformans strain-related differences [10]. Previous work on the polysaccharide capsule of switch variants has shown that phenotypic switching can alter not only capsule size but also both the biochemical as well as the biophysical properties of the capsular polysaccharide [14,15,17]. These changes can involve the position of the glucuronic acid on the mannose backbone as well as the distribution of charged residues over the mannose backbone.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Consistent with this view are the findings that Oacetylation of alginate in Pseudomonas aeruginosa contributed to biofilm formation [19] and the C. neoformans strain-related differences [10]. Previous work on the polysaccharide capsule of switch variants has shown that phenotypic switching can alter not only capsule size but also both the biochemical as well as the biophysical properties of the capsular polysaccharide [14,15,17]. These changes can involve the position of the glucuronic acid on the mannose backbone as well as the distribution of charged residues over the mannose backbone.…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, the characteristics of C. neoformans phenotypic switching during biofilm formation were investigated. These phenotypes show variations in their capsular polysaccharide [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, after the initial rapid clearance in wild-type and factor B-deficient animals, the remainder cleared at approximately the rate seen in C3-deficient mice, suggesting that these organisms represented a subpopulation that was not opsonized. Heterogeneity in capsule composition is known to occur in Cryptococcus (17) and may explain the second clearance phase.…”
Section: Discussionmentioning
confidence: 99%
“…neoformans isolates (serotypes A and D). In RC2, phenotypic switching alters the biophysical and biochemical properties of GXM [37]. Viscosity data in solutions of different ionic strength, suggest that the spacing of GlcpA along the Mannose backbone differs between the GXM of the RC2-SM and that of the RC2-MC strain.…”
Section: Differences In Gxm Of Rc2 and Np1mentioning
confidence: 99%